The F-word : how do overweight and obese Malay women experience and cope with fat stigma in Singapore? - Syarafina Abdul Halim. (2013)
The ideal body is the thin body, while a fat body is considered a deviant one. Women face especially narrowing standards of what kind of body is considered acceptable. It would thus be pertinent to attempt an understanding how women come to terms with fatness and cope with the stigma attached. However, much of the available research on fatness has left out the input of fat people themselves. Likewise, Singapore-based studies have neglected to address Malay women’s perspectives as distinct and separate from the general majority-Chinese population. Ten in-depth interviews were thus conducted with Malay women between 21 and 30 years old regarding their experiences with being fat in Singapore. Findings revealed what factors that led to their adoption of a fat identity, as well as how these women employ certain strategies to cope with the stigmatization of their fatness.